Effectiveness of hands-on cardiopulmonary resuscitation practice with self-debriefing for healthcare providers: A simulation-based controlled trial. Issue 6 (November 2017) - Fan, Hsuan-Jui; You, Shih-Hao; Huang, Chien-Hsiung; Seak, Chen-June; Ng, Chip-Jin; Li, Wen-Cheng; Lin, Chi-Chun; Weng, Yi-Ming
Introduction: The psychomotor skill of cardiopulmonary resuscitation emphasized the importance of high-quality chest compression. This investigation examined the effect of self-debriefing and the different materials of debriefing during hands-on cardiopulmonary resuscitation practice for healthcare providers. Methods: This was a randomized controlled trial of a cardiopulmonary resuscitation training program involving emergency medical technicians in northern Taiwan. Participants were blinded to the study purpose and were allocated randomly using the black envelope method. All participants completed a 2-min pre-test of hands-only cardiopulmonary resuscitation using a manikin. Those who were allocated to the control group received self-debriefing with knowledge of pre-test result. Those who were allocated to the experimental group received self-debriefing with an additional biomechanical information of performance of chest compression. A post-test was performed 30 min after the pre-test. Results: A total of 88 participants were enrolled with 44 in each group. There was significant difference of cardiopulmonary resuscitation quality after self-debriefing among all participants (pre- vs post-test adequate rate, 54.7% vs 67.5%, p = 0.028; adequate depth, 41.2% vs 69.5%, p < 0.001; full recoil, 35.9% vs 54.5%, p = 0.001). The analysis of effects of self-debriefing with additional knowledge of performance revealed no significant difference in any of the measurements (improvement in adequate rate, 11.3% vs 14.2%, p = 0.767; adequate depth, 29.6% vs 27.0%, p = 0.784; full recoil, 23.0% vs 14.1%, p = 0.275). Conclusion: Self-debriefing improved hands-only cardiopulmonary resuscitation quality whether or not biomechanical information of performance of chest compression was given.